Mitoxantrone-Loaded Nanoferritin Slows Tumor Growth and Improves the Overall Survival Rate in a Subcutaneous Pancreatic Cancer Mouse Model - Giamaica Conti (MDPI AG, 2021)
Pancreatic cancer (PC) represents an intriguing topic for researchers. To date, the prognosis of metastasized PC is poor with just 7% of patients exceeding a five-year survival period. Thus, molecular modifications of existing drugs should be developed to change the course of the disease. Our previously generated nanocages of Mitoxantrone (MIT) encapsulated in human H-chain Ferritin (HFt), designated as HFt-MP-PASE-MIT, has shown excellent tumor distribution and extended serum half-life meriting further investigation for PC treatment. Thus, in this study, we used the same nano-formulation to test its cytotoxicity using both in vitro and in vivo assays. Interestingly, both encapsulated and free-MIT drugs demonstrated similar killing capabilities on PaCa44 cell line. Conversely, in vivo assessment in a subcutaneous PaCa44 tumor model of PC demonstrated a remarkable capability for encapsulated MIT to control tumor growth and improve mouse survival with a median survival rate of 65 vs. 33 days for loaded and free-MIT, respectively. Interestingly, throughout the course of mice treatment, MIT encapsulation did not present any adverse side effects as confirmed by histological analysis of various murine tissue organs and body mass weights. Our results are promising and pave the way to effective PC targeted chemotherapy using our HFt nanodelivery platforms.